Sosialisasi Daur Ulang Sampah Sebagai Upaya Pengembangan Eko-Budaya di Lingkungan Desa Sayang Jatinangor Kabupaten Sumedang - Rijati, Sri; Intan, Tania; Subekti, Mega (Dewan Pimpinan Daerah (DPD) Forum Dosen Indonesia JATIM, 2017)
This activity aims to growth awareness and public concern over the use of household waste. One effective way is tomake the process of recycling of waste in order to be a new product that has economic value. Sayang village, Jatinangor inSumedang district became one of priority area for the organization of this event. Its geographical location which is relativelyclose to the area of education is one reason for choosing this village. The activities in the form of Program Pengabdian kepadaMasyarakat Dosen (PPMD) is carried out by means of lectures, demonstrations and practices / trainings. The high productionof household waste and negative behaviour regarding garbage is actually an issue that is closely related to cultural behaviour.Therefore, the solution is actually should be also related with the issue of people?s mindset about the garbage. Recycling wastebins in order to produce a product that has economic value to be an alternative way to change people's mindsets about thegarbage that have tended to be negative. This activity is considered successful because of the participation of the public,especially mothers of households is quite high and active in a series of events